PENGGUNAAN POTENTIALLY INAPPROPRIATE MEDICATIONS (PIMs) PADA PASIEN GERIATRI RAWAT INAP OSTEOARTHRITIS DI RS PKU MUHAMMADIYAH YOGYAKARTA - Andi Namirah Muh. Syuaib AS; Endang Darmawan; Mustofa Mustofa (Universitas Ahmad Dahlan, 2015)
Potentially inappropriate medications (PIMs) use among elderly is a serious public health problem because it is intrinsically linked to increased morbidity, mortality, and healthcare costs. This studyÂ aims to determine the association between number of drug prescribed, duration of hospital stay and PIMs use among elderly hospitalized patients at PKU Muhammadiyah Yogyakarta General Hospital. This study was analytic observational with cross-sectional study. Beers criteria 2012 were used to identify PIMs use among elderly hospitalized patients with osteoarthritis. Logistic regression analysis were used to determine association between number drugs of prescribed, duration of hospital stay and PIMs use. The results showed that 7 (38.9%) out of 18 hospitalized elderly patients were identified PIMs use and all of patients received atleast one PIM. The most common agents involved in PIMs were estazolam (11.1%), and metoclopramide (11.1%). Polypharmacy is a major predictor factor of PIMs use in this study.